Search Menu

Contents

Factoring Trinomials

page 1 of 2

Factoring Trinomials

Page 1

Page 2

Factoring Trinomials

Factoring Trinomials

Factoring Trinomials

Factoring Trinomials of the Form x2 + bx + c and x2 - bx + c

Just as the product of two binomials can often be rewritten as a trinomial, trinomials of the form ax2 + bx + c can often be rewritten as the product of two binomials. For example, x2 + 3x + 2 = (x + 1)(x + 2).

We now know that the product of two binomials of the form (x + d ) and (x + e) is given by:

(x + d )(x + e) = x2 + xe + dx + de = x2 + (d + e)x + de    

Thus, in order to rewrite a binomial x2 + bx + c as the product of two binomials (b positive or negative), we must find numbers d and e such that d + e = b and de = c. Since c is positive, d and e must have the same sign.

Here are the steps to factoring a trinomial of the form x2 + bx + c, with c > 0. We assume that the coefficients are integers, and that we want to factor into binomials with integer coefficients.

  1. Write out all the pairs of numbers which can be multiplied to produce c.
  2. Add each pair of numbers to find a pair that produce b when added. Call the numbers in this pair d and e.
  3. If b > 0, then the factored form of the trinomial is (x + d )(x + e). If b < 0, then the factored form of the trinomial is (x - d )(x - e).
  4. Check: The binomials, when multiplied, should equal the original trinomial.
Note: Some trinomials cannot be factored. If none of the pairs total b, then the trinomial cannot be factored.

Example 1: Factor x2 + 5x + 6.

  1. Pairs of numbers which make 6 when multiplied: (1, 6) and (2, 3).
  2. 1 + 6≠5. 2 + 3 = 5. Thus, d = 2 and e = 3 (or vice versa).
  3. (x + 2)(x + 3)
  4. Check: (x + 2)(x + 3) = x2 +3x + 2x + 6 = x2 + 5x + 6
Thus, x2 + 5x + 6 = (x + 2)(x + 3).

Example 2: Factor x2 - 7x + 12.

  1. Pairs of numbers which make 12 when multiplied: (1, 12), (2, 6), and (3, 4).
  2. 1 + 12≠7. 2 + 6≠7. 3 + 4 = 7. Thus, d = 3 and e = 4.
  3. (x - 3)(x - 4)
  4. Check: (x - 3)(x - 4) = x2 -4x - 3x + 12 = x2 - 7x + 12
Thus, x2 - 7x + 12 = (x - 3)(x - 4).

Example 3: Factor 2x3 +4x2 + 2x.
First, remove common factors: 2x3 +4x2 +2x = 2x(x2 + 2x + 1)

  1. Pairs of numbers which make 1 when multiplied: (1, 1).
  2. 1 + 1 = 2. Thus, d = 1 and e = 1.
  3. 2x(x + 1)(x + 1) (don't forget the common factor!)
  4. Check: 2x(x + 1)(x + 1) = 2x(x2 +2x + 1) = 2x3 +4x2 + 2x
Thus, 2x3 +4x2 +2x = 2x(x + 1)(x + 1) = 2x(x + 1)2.
x2 + 2x + 1 is a perfect square trinomial.

Page 1

Page 2